2008
DOI: 10.1182/blood-2007-09-109876
|View full text |Cite
|
Sign up to set email alerts
|

Factor H autoantibodies in atypical hemolytic uremic syndrome correlate with CFHR1/CFHR3 deficiency

Abstract: Atypical hemolytic uremic syndrome (aHUS) is a severe renal disease that is associated with defective complement regulation caused by multiple factors. We previously described the deficiency of factor H-related proteins CFHR1 and CFHR3 as predisposing factor for aHUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
303
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 330 publications
(323 citation statements)
references
References 26 publications
11
303
2
4
Order By: Relevance
“…Patients who have aHUS with combined mutations have been reported (4). Approximately 10% of children with aHUS have an acquired functional CFH deficiency caused by anti-CFH autoantibodies, frequently associated with absent CFHR1/ CFHR3 (11)(12)(13). In mutation carriers, aHUS penetrance is approximately 50%, suggesting that other genetic or environmental modifiers are needed for disease expression (3).…”
Section: H Emolytic Uremic Syndrome (Hus) Is a Clinical Triad Ofmentioning
confidence: 99%
“…Patients who have aHUS with combined mutations have been reported (4). Approximately 10% of children with aHUS have an acquired functional CFH deficiency caused by anti-CFH autoantibodies, frequently associated with absent CFHR1/ CFHR3 (11)(12)(13). In mutation carriers, aHUS penetrance is approximately 50%, suggesting that other genetic or environmental modifiers are needed for disease expression (3).…”
Section: H Emolytic Uremic Syndrome (Hus) Is a Clinical Triad Ofmentioning
confidence: 99%
“…Bacteria (10 4 CFU) were incubated in 5% NHS diluted either in DGVB ϩϩ or 10% FH-depleted serum prepared as described previously (38) in a final volume of 100 l. At different time points, 10-l aliquots were removed and spread onto chocolate agar plates. After 18 h of incubation at 37°C, CFUs were determined.…”
Section: Serum Bactericidal Assaymentioning
confidence: 99%
“…7 We have also shown that NAHR in this region leads to deletions incorporating CFHR3/CFHR1 and CFHR1/CFHR4, which are associated with the presence of fH autoantibodies in aHUS. [8][9][10] We routinely use multiplex ligation-dependent probe amplification (MLPA) 11 to screen for genomic disorders in aHUS. In this study, we report the finding of a deletion in the C terminal region of CFH in a large aHUS family.…”
Section: Introductionmentioning
confidence: 99%